Social focus of the educational activity of the university: Declaration of goals and practice - E. S. Sakharchuk; E. R. Bagramyan; I. A. Kiseleva; A. L. Sakharchuk (Образование и наука)
Introduction. These days, destructive manifestations among young people can be observed, and the main reason for it may be the global value and worldview crisis. It consists in the discrepancy of ideals, values, beliefs, knowledge to the tasks of overcoming the instability of modern civilisation. Due to this, there is a need to update the educational questions, which have a so-called “social focus”. Among these are: developing the “human” in a person, overcoming disunity (e.g. egoism, individualism), developing social responsibility, etc. In this regard, two factors are of an urgent nature: firstly, systematic studies of the students’ socio-cultural identity, and, secondly, the study of the university socio-cultural environment, which influences overcoming the negative consequences of individualism and disunity in the university environment. The focus on the social side of education presupposes the formation of value community in the university environment, while the characteristics of the socio-cultural identity of the members in educational activity and the consideration of research results in practice become decisive.Aim. The aim of the present research work was to identify the conditions of extra-curricular educational activities. These conditions contribute to the formation of a value community in the university environment based on common spiritual and moral ideas. The specific objectives of the research are related to the following aspects: identification of the dominant conceptual approaches to the implementation of educational activities in the system of modern Russian higher education (with a focus on the social focus demanded by society); determination of the differentiated composition of the subjects of educational activity as one of the factors, which determine the cultural identification of students and the development of communities in the socio-cultural environment; establishment of the relevance of diagnostic tools which allow students to track the development of positive social qualities; the disclosure of the general orientation of educational activities in extra-curricular time with social and personal focus.Methodology, methods and techniques. In the course of the research, a qualitative and quantitative content analysis of educational work programmes in 12 universities (multi-profile, humanities and technical) from different regions of the Russian Federation was carried out. The research is based on the environmental approach in education. The research is based on the methodology of the environmental approach in pedagogy and the idea of the event-based mechanism of education. The interpretations of the social focus of students’ world outlook orientations are based on the theory of basic personal values.Results. The conditions of extra-curricular educational activity are revealed: goal-setting of extra-curricular activities, which has a predominantly social focus; correspondence of the content of educational activities to the tasks of overcoming individualism and disunity; consideration of the differentiated composition of the subjects of educational activity. The authors posed the scientific problem for a diagnostic apparatus that allows universities to track the process and results of educational work aimed at the development of social values.Scientific novelty. The authors have made a proposal on the need to take into account the differentiated set of members of educational activity with a focus on public interests in priority.Practical significance. The conclusions, which justify the need to consider the moral and ideological positions in order to achieve results in the development of the socially focused qualities, may be of interest to specialists involved in designing and organising educational activities in universities.